Anatomical study of single incision contralateral C7 nerve transfer through subdural pathway - Yao, Long; Yan, Zhengcun; Wang, Xiaodong; Gu, Jiaxiang; Liu, Hongjun; Zhang, Hengzhu (Frontiers in Neuroanatomy, 2024)
Objective To explore the feasibility of single incision C7 nerve transfer surgery through the subarachnoid pathway on the healthy side through anatomical research. Method Four fresh frozen cadaver specimens were used for the study. Observe and measure the length of C7 nerve root fibers. Divide the front root into 3 bundles and the rear root into 5 bundles. Result The C7 nerve has a filamentous structure, arranged symmetrically on both sides, and the length of the root fibers gradually shortens from top to bottom. The length of the left anterior root decreased from (12.25 ± 0.68) mm to (9.75 ± 1.40) mm, the length of the right anterior root decreased from (12.95 ± 1.49) mm to (10.00 ± 2.00) mm, the length of the left posterior root decreased from (15.63 ± 1.55) mm to (12.38 ± 0.71) mm, and the length of the right posterior root decreased from (15.48 ± 1.37) mm to (12.30 ± 0.90) mm. The distance from the exit of the C7 nerve from the dura mater to the fusion site in 4 specimens was (10.98 ± 1.21) mm on the left and (10.98 ± 1.391) mm on the right. All four specimens have completed nerve bundle anastomosis. Conclusion From an anatomical perspective, it is feasible to anastomose the healthy side C7 nerve with the affected side root fibers in the dorsal bundle of the spinal cord after cutting off the dura mater.